(untitled) (Journal of Educational Sciences, 2017)
The article is dedicated to the national educational policies and priorities for intercultural education in Bulgaria regarding the discipline Ethnopsychology, taught at the Faculty of History, Bachelor’s Degree specialties:Ethnology, History and Philosophy, and Master’s Degree ones: Education in History for the Secondary Education, Historic-Ethnic Models of National Security. Principles and approaches are identified to encourage socio-cultural competence in teachers in the context of higher education in the Bulgarian educational system. Paradigms regarding the standard «Civic, heath, ecological and intercultural education» of the Ministry of Education of Bulgaria (2016), in accordance with the Preschool and School Education Act (2016), are clarified. The problems of educational integration of minorities in Bulgaria are highlighted. A piloted empirical-theoretical model from the point of view of ethno-psychology is presented. Discusses reflective and encouraging Directive documents of the National Council for cooperation on ethnic and Integration issues of Council of Ministers and the Ministry of education and science.